The Assessment of Leadership Competencies in First-Year Undergraduate Medical Students - Cabell, Grant Hayden; Prado, Isabel; Price, Meghan; Sullivan, Meghan; Peterson, Cecily K.; Fuller, Anthony T.; Doty, Joseph P.; Taylor, Dean C. (Journal of Education and Training, 2023)
This study aimed to assess the views and leadership competencies of incoming medical students and determine whether leadership traits predicted patient-centeredness in these students. Incoming medical students at one institution from 2017-2020 (N=428) completed a Leadership Needs Assessment assessing self-reported ability and the importance of competency in teamwork, selfless service, integrity, critical thinking, and emotional intelligence. Participants in the entering class of 2020 (n=92) also completed the Johns Hopkins University Patient-Centeredness Assessment to evaluate patient-centered attitudes. This cohort repeated both surveys at the completion of the first year to assess for changes in the perceived importance of leadership qualities, self-reported competencies, and patient-centeredness. Participants self-reported the highest competency (mean, SD) in integrity (7.92, 1.19) and the lowest in critical thinking (6.59, 1.12). Leadership Development Opportunity (difference between leadership expectation and self-reported ability) was largest in teamwork (2.31, 1.11) and smallest in integrity (0.97, 1.18). Post-first-year assessments were compared in the 2020 cohort, and statistically significant increases (mean, p-value) were found in critical thinking (0.31, p<0.01), emotional intelligence (0.18, p<0.03), and patient-centeredness (0.92, p<0.05). Patient-centeredness was positively predicted by integrity and negatively predicted by critical thinking. Incoming medical students highly value leadership and enter medical school with a robust self-reported ability level. Our data suggest that integrity may increase patient-centeredness and that incoming medical students perceive teamwork as the greatest area for leadership competency development. Further research is needed to determine the best curricula to develop leadership competencies and increase patient-centeredness.